On the instability of two entropic dynamical models. (October 2016) - Henry, Guillermo; Rodriguez, Daniela
Abstract: In this paper we study two entropic dynamical models from the viewpoint of information geometry. We study the geometry structures of the associated statistical manifolds. In order to analyse the character of the instability of the systems, we obtain their geodesics and compute their Jacobi vector fields. The results of this work improve and extend a recent advance in this topics studied in Peng et al.[13].